Granulation and ferric oxides loading enable biochar derived from cotton stalk to remove phosphate from water - Ren, Jing; Li, Nan; Li, Lei; An, Jing-Kun; Zhao, Lin; Ren, Nan-Qi (Bioresource technology, 2015)
[Display omitted] •Granulation followed by ferric loading had the best phosphate adsorption capacity.•The phosphate adsorption capacity was increased from 0 to 0.963mg/g.•Both granulation and ferric oxides loading obviously increased the surface areas.•Pseudo-first order model is allowable to estimate the adsorption kinetics. Granulation of biochar powder followed by immobilization of ferric oxides on the macroporous granular biochar (Bg-FO-1) substantially enhanced phosphate removal from water. BET analysis confirmed that both granulation and ferric oxides loading can increase the surface areas and pore volumes effectively. Bg-FO-1 was proven to be a favorable adsorbent for phosphate. The phosphate adsorption capacity was substantially increased from 0mg/g of raw biochar powder to 0.963mg/g (Bg-FO-1). When the ferric oxides loading was prior to granulation, the adsorption capacity was decreased by 59–0.399mg/g, possibly due to the decrease of micropore and mesopore area as well as the overlaying of binders to the activated sites produced by ferric oxides.